2019
DOI: 10.1246/cl.180930
|View full text |Cite
|
Sign up to set email alerts
|

Complexation between MOTf (M = Li and Na) and N-Phosphine Oxide-substituted Imidazolylidenes via Coordination of the N-Phosphoryl Groups

Abstract: A reaction between an N-phosphine oxide-substituted imidazolylidene (PoxIm) and MOTf (M = Li or Na) in THF afforded the complexes [(PoxIm) x (MOTf) y (THF) z ] through the coordination of the N-phosphoryl group to Na + or Li + , which was unambiguously confirmed by 13 C and 31 P NMR spectroscopy and single-crystal X-ray diffraction analyses. These measurements confirmed that the carbene moieties in these complexes remain intact. In solution, PoxIm and MOTf might form the complexes in a 3:2 ratio (i.e., x = 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…We have included in our study carbene precursors 1 , 2 , and 5 , previously reported by Hoshimoto (Scheme ). The preparation of these precursors is straightforward and is accomplished by oxidation with hydrogen peroxide of the known parent N -phosphanyl imidazolium or N , N ′-diphosphanyl-imidazolium salt to yield 1 , 2 , and 5 as air- and moisture-stable compounds. Subsequent deprotonation of the precursors at C-2 with KHDMS furnishes the free carbenes 3 , 4 , and 6 , which can be isolated and characterized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have included in our study carbene precursors 1 , 2 , and 5 , previously reported by Hoshimoto (Scheme ). The preparation of these precursors is straightforward and is accomplished by oxidation with hydrogen peroxide of the known parent N -phosphanyl imidazolium or N , N ′-diphosphanyl-imidazolium salt to yield 1 , 2 , and 5 as air- and moisture-stable compounds. Subsequent deprotonation of the precursors at C-2 with KHDMS furnishes the free carbenes 3 , 4 , and 6 , which can be isolated and characterized.…”
Section: Resultsmentioning
confidence: 99%
“…All solvents were purified and dried by standard methods. Ligand precursors 1 , 2 , and 5 as well as starting complex [PdCl 2 ­(BN) 2 ] were prepared according to standard procedures. NMR spectra were recorded on Bruker Avance spectrometers working at 300 MHz (300.1 MHz for 1 H, 75.5 MHz for 13 C, 282.2 MHz for 19 F, and 121.5 MHz for 31 P); chemical shifts (δ) are reported in units of ppm relative to the residual solvent signals and to external 85% H 3 PO 4 (for 31 P).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A) (25,26). To date, (S)PoxIms have demonstrated various coordination modes toward metals, including coordination by only the carbene atom (-C) (27,28), by only the N-phosphinoyl oxygen atom (-O) (29,30), and by both the carbene and oxygen atoms (-C,O) (31,32); however, dynamic coordination exchange between the -C and -C,O modes remains unknown.…”
Section: Main Textmentioning
confidence: 99%
“…Recently, we have proposed a concept of multifunctional multipurpose carbenes, i.e., carbenes that include functional groups applicable to a variety of purposes beyond additional coordination sites. In this context, N -phosphine oxide-substituted imidazolylidene (PoxIm) and the corresponding imidazolinylidene (SPoxIm) represent pioneering examples (Figure A).…”
Section: Introductionmentioning
confidence: 99%